PENGARUH REFORMASI ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI KASUS PADA KANTOR PELAYANAN PAJAK (KPP) PRATAMA SUMEDANG) - Fahrul Alam Masruri (Jurnal Akuntansi Bisnis dan Ekonomi, 2018)
This research was motivated by the launching of an activity program by the Directorate General of Taxation on medium-term tax administration reform (3-5 years). Administrative reform needs to be done to achieve a high level of compliance given the low increase in individual taxpayer compliance from year to year in Sumedang Regency. The study aims to determine how the influence of tax administration reforms on individual taxpayer compliance. The method used in this study is a survey method with a descriptive analysis approach, with sampling using the Slovin formula. The technique of collecting data uses interviews, observation and literature studies. Data analysis is carried out quantitatively using product moment correlation test and f test. The results of the study obtained a correlation coefficient value of -0.261 and the degree of determination of the effect of tax administration reform on taxpayer compliance was 6.8% while 93.2% was influenced by other factors. Hypothesis testing results obtained f count value greater than f table (f count 4.964> f table 3.998) so that the hypothesis is accepted or there is the influence of tax administration reform on individual taxpayer compliance at Sumedang Primary Tax Office.